A multiple matrix model to study the population dynamics of R. appendiculatus in Zimbabwe - Mwambi, H.G.; Odhiambo, J.W.; Duchateau, L. (International Biometric Society, 1997)
The classical Leslie matrix methodology is extended to describe the life cycle of the brown ear tick (R. appendiculatus), incorporating both within and between stage transitions of the population. We use data from the highveld of Zimbabwe Reported in Short et al. (1989a,b). The model incorporates the seasonality patterns in the site by means of a matrix chain which is a matrix product describing the seasonal cycle in the year. It is shown that the overall population growth is governed by the dominant eigenvalue of the matrix chain representing the seasonal cycle. The sensitivity of this growth factor to population parameters is investigated and its implication to control strategies discussed.